DNA methylation as a mediator of genetic and environmental factors in type 1 diabetes and autoimmunity - Pahkuri, Sirpa (fi=Turun yliopisto|en=University of Turku|, 2026)
Type 1 diabetes (T1D) is a chronic autoimmune disease which often develops during childhood in genetically susceptible individuals and is most likely triggered by some environmental factors. Around 40–50% of the genetic risk is conferred by HLA class II genes HLA-DRB1, -DQA1 and -DQB1. In addition, single nucleotide polymorphisms (SNPs) in genes, such as INS, PTPN22 and IL2RA, contribute by smaller effects. However, many T1D-associated SNPs are located in non-coding region and their effects are still unclear. The aim of this thesis was to examine the effect of T1D-associated genetic variation and early antibiotic exposure on DNA methylation in lymphocytes, in order to clarify their mechanisms and examine whether DNA methylation could mediate their effects in T1D and autoimmunity. T1D-associated SNPs rs689 in INS and rs12722495 in IL2RA were found to be associated with DNA methylation in INS and IL2RA promoters, suggesting that DNA methylation may mediate the effect of some SNPs on T1D risk. However, only one CpG site had T1D-associated methylation changes in INS when analyzing methylation in INS, IL2RA and PTPN22, suggesting that T1D may have some effects on methylation but they may be cell specific with small effects. The effect of T1D susceptibility-associated HLA class II haplotypes, DRB1*03-DQA1*05-DQB1*02 (DR3-DQ2) and DRB1*04:01-DQA1*03-DQB1*03:02 (DR4-DQ8), and protection associated haplotype, DRB1*15-DQA1*01-DQB1*06:02 (DR2-DQ6), on epigenome-wide methylation was localized to HLA region, especially HLA-DRB1 locus, where the protective haplotype DR2-DQ6 was associated with hypomethylation. Antibiotic exposure during the first week of life was not associated with changes in immune cell frequencies in PBMC at the age of 3 months but it had effects on CD4+ and CD8+ T cell epigenome. These results suggest that both T1D-associated genetic variation and early antibiotic exposure can affect DNA methylation in lymphocytes and that methylation could mediate at least part of their effects in T1D and autoimmunity.

DNA-metylaation rooli geneettisen variaation ja ympäristötekijöiden vaikutuksen välittäjänä tyypin 1 diabeteksessa ja autoimmuniteetissa Tyypin 1 diabetes (T1D) on krooninen autoimmuunitauti, joka kehittyy usein jo lapsuudessa geneettisesti alttiissa henkilöissä ja todennäköisesti jonkin tai joidenkin ympäristötekijöiden laukaisemana. HLA luokka II geenit HLA-DRB1, -DQA1 ja -DQB1 selittävät geneettisestä alttiudesta noin 40–50 % ja lisäksi monilla yhden nukleotidin mutaatioilla (engl. single nucleotide polymorphism, SNP) geeneissä, kuten INS, PTPN22 ja IL2RA, on vaikutusta. Monet näistä mutaatioista sijaitsevat DNA:n koodaamattomalla alueella eikä niiden vaikutuksia vielä täysin tunneta. Väitöstutkimuksen tavoitteena oli tarkastella tyypin 1 diabetekseen liitetyn geneettisen variaation ja varhaisen antibioottialtistuksen vaikutusta DNA-metylaatioon immuunisoluissa ja selvittää voisiko DNA-metylaatio toimia niiden vaikutuksen välittäjänä T1D:n ja autoimmuunireaktioiden kehityksessä. T1D-alttiuteen liitettyjen SNP-mutaatioiden rs689 (INS) ja rs12722495 (IL2RA) havaittiin olevan yhteydessä INS- ja IL2RA-geenien metylaatioon. Tutkittaessa koko epigenomia, T1D-alttiuteen liitettyjen HLA luokka II haplotyyppien DRB1*03-DQA1*05-DQB1*02 (DR3-DQ2) ja DRB1*04:01-DQA1*03-DQB1*03:02 (DR4-DQ8), sekä suojaavan haplotyypin, DRB1*15-DQA1*01-DQB1*06:02 (DR2-DQ6), vaikutus keskittyi HLA-alueelle, erityisesti HLA-DRB1 geeniin, jonka hypometylaatio oli yhteydessä suojaavaan DR2-DQ6-haplotyyppiin. Ensimmäisen elinviikon aikana saatu antibioottikuuri ei ollut yhteydessä immuunisolujen frekvenssien muutoksiin 3 kk:n iässä otetuissa PBMC-näytteissä, mutta se oli yhteydessä CD4+ ja CD8+ T-solujen epigenomin muutoksiin. Nämä tulokset viittaavat siihen, että tyypin 1 diabetekseen liitetty geneettinen variaatio sekä varhainen antibioottialtistus voivat vaikuttaa immuunisolujen DNA-metylaatioon, mikä voisi toimia niiden vaikutuksen välittäjänä T1D:n ja autoimmuniteetin kehityksessä.